2006
DOI: 10.1136/bjsm.2006.030205
|View full text |Cite
|
Sign up to set email alerts
|

Do circulating leucocytes and lymphocyte subtypes increase in response to brief exercise in children with and without asthma?

Abstract: Background: Exercise can alter health in children in both beneficial (eg reduced long-term risk of atherosclerosis) and adverse (eg exercise-induced asthma) ways. The mechanisms linking exercise and health are not known, but may rest, partly, on the ability of exercise to increase circulating immune cells. Little is known about the effect of brief exercise, more reflective of naturally occurring patterns of physical activity in children, on immune cell responses. Objectives: To determine whether (1) a 6-min bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 41 publications
2
16
0
2
Order By: Relevance
“…As little as 70 s of stair climbing has been shown to increase the frequency of NK cells in the blood by 6-fold [16]. Subsequently, several studies have shown mobilization of NK cells within minutes with exercise, when performed with an intensity associated with breathlessness, increased heart rate, and elevated plasma epinephrine levels [17][18][19]. In general, maximal mobilization of NK cells is Glossary Antibody-dependent cellmediated cytotoxicity (ADCC): mechanism of immune-mediated killing of antibody coated target cells.…”
Section: Exercise and The Control Of Nk Cell Mobilizationmentioning
confidence: 97%
“…As little as 70 s of stair climbing has been shown to increase the frequency of NK cells in the blood by 6-fold [16]. Subsequently, several studies have shown mobilization of NK cells within minutes with exercise, when performed with an intensity associated with breathlessness, increased heart rate, and elevated plasma epinephrine levels [17][18][19]. In general, maximal mobilization of NK cells is Glossary Antibody-dependent cellmediated cytotoxicity (ADCC): mechanism of immune-mediated killing of antibody coated target cells.…”
Section: Exercise and The Control Of Nk Cell Mobilizationmentioning
confidence: 97%
“…In both adults and children, a leukocytosis occurs following brief, heavy exercise (29). In addition, we now know from recent studies performed in this and other laboratories that there are remarkable changes in the gene expression profile pattern of the circulating leukocytes rapidly accompanying exercise (2,4,9,25).…”
mentioning
confidence: 89%
“…Paradoxically, exercise leads to an acute increase in immune cells and mediators in the peripheral blood and many of these changes are also known to be involved in the allergic response. 3,4 The factors that prevent allergic responses such as rhinitis and bronchoconstriction from occurring in everyone upon exercise despite immune activation remain unknown. Higher rates of respiratory infection, congestion, and allergy and asthma have been reported in endurancetrained athletes.…”
Section: Introductionmentioning
confidence: 99%